Theorising Rome - Evans, Rhiannon (Cambridge Scholars Publisher, 2021)
Theorising Rome asks the questions: what did 'Rome'--the physical location, the political entity, the literary construct--mean in antiquity? Equally, what has it meant in subsequent centuries? This volume addresses these broad questions in a number of complementary ways, and each chapter shows that ancient Rome has been recontextualised and remade--and, in fact, re-theorised--by successive historical periods and literary genres to perform their cultural labour. The contributions here approach this question through the lens of Roman literary, historical and philosophical texts, as well as recep.